H∞ generalized dynamic unknown inputs observer design for discrete LPV systems. Application to wind turbine. (November 2018) - Pérez-Estrada, Abraham-Jashiel; Osorio-Gordillo, Gloria-Lilia; Alma, Marouane; Darouach, Mohamed; Olivares-Peregrino, Víctor-Hugo
Abstract: This paper concerns the design of a generalized dynamic observer (GDO) for unknown inputs discrete-time linear parameter varying (LPV) systems. The structure of this observer generalizes the existing ones of the proportional observer (PO) and proportional integral observer (PIO). Conditions for the existence and stability of this observer are given through parameter dependent Lyapunov (PDL) function and its design is obtained in terms of a set of linear matrix inequalities (LMIs). The efficiency of the proposed observer, compared to particular cases of this structure, as the PO and PIO, is illustrated by a 4.8 MW wind turbine system.